2012
DOI: 10.1002/j.1556-6676.2012.00058.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of School Bonding on High School Seniors’ Academic Achievement

Abstract: The authors examine the effects of school bonding on academic achievement (measured by math achievement scores) in a sample of 12th graders from the Educational Longitudinal Study of 2002 (Ingels, Pratt, Rogers, Siegel, & Stutts, 2005). Components of school bonding have proximal and distal effects on academic achievement. Attachment to school and school involvement had direct effects on achievement; attachment to teachers and school commitment behaviors had indirect effects on achievement through school‐relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 57 publications
(118 reference statements)
7
98
0
2
Order By: Relevance
“…They were found to be typical of educational settings in a wide range of countries; schools try to attract students by advertising a range of extracurricular activities. On occasion, extra-curricular activities have been even included into governmental education planning documentation (Bryan et al 2012;Nealon, 1950;Vermaas et al, 2009). …”
Section: Eca Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They were found to be typical of educational settings in a wide range of countries; schools try to attract students by advertising a range of extracurricular activities. On occasion, extra-curricular activities have been even included into governmental education planning documentation (Bryan et al 2012;Nealon, 1950;Vermaas et al, 2009). …”
Section: Eca Overviewmentioning
confidence: 99%
“…Most available studies of ECAs were conducted in secondary school contexts. Earlier research studies included mostly drama clubs, sports, debate clubs, music, sports, and similar activities (e.g., McCarthy, 2000;Bryan et al, 2012;Dumais, 2009). These studies demonstrated multiple positive effects of ECAs on grades overall and on grades in specific subjects, such as mathematics, science and English (Mahoney, 2000;McLure & McLure, 2000;Fredricks & Eccles, 2008;Dumais, 2009;Knifsend & Graham, 2012).…”
Section: History Of Ecas In Secondary and Postsecondary Educationmentioning
confidence: 99%
“…These students do not study, receive poor grades and feel alienated by the school itself. Furthermore, the Bryan et al (2012) study showed students who reported disliking school had significantly lower academic achievement scores. Whether emphasizing the relationship between student and school or student and parent, all studies have one thing in common, attachment is the influencing factor.…”
Section: Adolescents and School Attachmentmentioning
confidence: 98%
“…Students who have a bond or feel an attachment to their school show higher levels of academic achievement (Bryan et al, 2012) and have higher GPAs (LeCroy & Krysik, 2008). This may be due to the fact that students with secure attachment styles are more often embedded in their school and they tend to try harder and participate more in class (Dykas & Cassidy, 2011).…”
Section: Self-efficacy and Self-worthmentioning
confidence: 99%
See 1 more Smart Citation